Coping Style in Glioma Patients and Their Caregiver: Evaluation During Disease Trajectory - Guariglia, Lara; Ieraci, Sonia; Villani, Veronica; Tanzilli, Antonio; Benincasa, Dario; Sperati, Francesca; Terrenato, Irene; Pace, Andrea (Frontiers in Neurology, 2021)
Background: Patients with glioma have a poor prognosis and, in a short period of time, have to deal with severe forms of disability, which compromise their psychological distress and quality of life. The caregivers of these patients consequently carry a heavy burden in terms of emotional and patient care. The study aims to evaluate the coping strategies of patients and their caregivers during the course of the disease in order to frame the adaptation process in a rapidly progressing pathology. Methods: A prospective study on 24 dyads of patients affected by malignant glioma and their caregivers was conducted between May 2016 and July 2018. Questionnaires designed to identify the coping style (MINI-MaC Scale) and psychological distress (HADS scores) and assess QOL (EQ-5D) were administered at two time points: at first lines of treatment and at disease recurrence. Results: Patients and their caregiver structure adaptive coping strategies during the disease: a coping style oriented toward a fighting spirit prevails at baseline (Mini-Mac Mean 3.23); fatalism prevails at recurrence (Mini-Mac Mean 3.03). Psychological distress affects the coping style expressed: high levels of anxiety symptoms were found to be significantly associated with a coping style oriented toward anxious preoccupation, helpless–hopeless, and fatalism; low depressive symptoms were inversely correlated with fighting spirit coping style. Patients' and caregivers' perceptions of quality of life were correlated between them and with performance status assessed by clinicians. In a dyadic perspective, the adaptation of a member of the couple varies as a function of the other partner's coping style. Conclusions: Our data are in line with previous literature on cancer patients, demonstrating that coping style is not a persistent dimension of personality, but can change depending on the situation. Despite the disease rapid course, patients and their caregivers can structure adaptive and functional defenses to manage the disease.